Roscovitine enhances the bactericidal activity of the airway surface liquid of the cystic fibrosis bronchial epithelium but does not protect against Pseudomonas aeruginosa infection - Adrien Maupas; Anaëlle Muggeo; Pierre Vermeulen; Sophie Moussalih; Edouard Sage; Emilie Luczka-Majérus; Christelle Coraux; Thomas Guillard (PLoS ONE, 2025)
Cystic fibrosis (CF) is the most common genetic diseases in the Caucasian population. CFTR defects, the most common being F508del, lead to abnormal mucus accumulation. Respiratory failure caused by the resulting chronic infections is the leading cause of death in people with cystic fibrosis (pwCF). Pseudomonas aeruginosa is a major pathogen in CF and is responsible for a deterioration of respiratory function in pwCF. The increase of antibiotic-resistant P. aeruginosa strains encourages the search for alternative therapeutics for treating P. aeruginosa infection. In vitro studies have shown an interest in (R)-roscovitine (roscovitine) in the fight against bacterial infection in pwCF. Here we show a nuanced effect of roscovitine on ASL bactericidal activity and CF bronchial epithelium protection against P. aeruginosa. Using a 3D model of fully differentiated and functional F508del-CFTR human bronchial epithelium, we evidenced (i) an enhancement of the bactericidal activity of the airway surface liquid for 25 μM roscovitine but (ii) no limitation of the dynamic of the epithelium destruction upon roscovitine treatment whatever the concentrations. Our findings shed light on reasons for the lack of beneficial effects to prevent P. aeruginosa infection in pwCF treated with roscovitine in the ROSCO-CF clinical trial. We anticipate that our findings would have significant therapeutic implications in seeking to optimize roscovitine analogs.